PERSPECTIVES OF FEEDSTOCK BASE EXPANSION FOR BIODIESEL FUEL PRODUCTION IN UKRAINE - Матвєєва, І. В.; Яковлєва, А. В.; Зубенко, С. О.; Гудзь, А. В. (Science-based technologies, 2019)
Article is devoted to the study of perspectives of feedstock base expansion for production of biodiesel fuels in Ukraine. It is shown that one of the most relevant problems of Ukrainian energy sector is shortening of consumption of own oilproducts. The state of fuel-energy and transport sector of Ukraine and, thus, the search for new renewable energy sources is considered. The overview of the modern state of biofuel industry, biodiesel fuels production in particular, is presented in the article. The main normative-technical documents in sphere of production and use of biodiesel fuel is given and analyzed. The available nowadays feedstock resources, which may be used for biodiesel fuel production were considered — all vegetable oils, which are typical for Ukraine (sunflower, soybean, corn), but more often rapeseed oil and comparatively new camelina oil. The comparative analysis of agronomical characteristics of rapeseed and camelina oils was done. It is shown that camelina is characterized by high cold-temperature and drought resistance, low needs in fertile soils and necessity in fertilizers and herbicides. Due to this the cost of camelina seeds is in two times lower than average. The comparative analysis of samples of biodiesel fuels based on methyl and ethyl esters of rapeseed oil and camelina oil was done. The advantages of using camelina oil instead of rapeseed oil as an alternative for production of biodiesel fuels were formulated and presented. It is shown that physical-chemical and exploitation properties of studied samples of biofuels, based on camelina oil in particular, completely satisfy requirements of standards for biodiesel fuel. In a result of this study we have done the conclusion that camelina oil can be effectively used for production of biodiesel fuel and also for using as a partial or total substituent of conventional oil-derived diesel fuel.